REGIONAL DEVELOPMENT STRATEGY FOR POVERTY REDUCTION (Studies on Poverty Reduction in Pasuruan Regency, East Java Province, Indonesia): Poverty reduction, Development Strategy, Poverty, Local government - Mardiyono (JAMAK: Jurnal Administrasi Manajemen dan Kepemimpinan, 2020)
A poverty reduction is a form of alleviating poverty to a certain level as the responsibility of the government to do so. The poverty reduction requires a planning strategy in assessing the dimensions of poverty causes such as determining priorities as an effective form of poverty reduction, and calling for synergetic cooperation amidt various parties involved. The cooperation between the government at various levels, the private sector and the community is absolutely necessary. Indonesia is a decentralized unitary state where the role of Local Government in combating poverty is very important. One of the local governments is the Pasuruan Regency with 13.8% poverty rate of its population. Therefore, the government launchs a program names the Pasuruan Development of Poverty Reduction Strategies with regard to the cooperation between sectors as mentioned.